2018
DOI: 10.1039/c8cy00491a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the reactivity of methoxyphenol positional isomers towards hydrogen-transfer reactions by ATR-IR spectroscopy of the liquid–solid interface of RANEY® Ni

Abstract: In the presence of Raney® Ni and 2-propanol, guaiacol is orientated parallel to the catalyst surface, whereas 3- and 4-methoxyphenol forms a titled adsorption surface complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…ATR-IR has been employed to understand the mechanism of methoxyphenol HDO/hydrogenolysis over RANEY Ni, for which C–O cleavage is favored under CTH conditions, but ring saturation occurs under H 2 . ATR-IR measurements suggest 2-methoxyphenol lies flat with the aromatic ring parallel to the surface, favoring demethoxylation (DMO) of 2-methoxyphenol to cyclohexanol under CTH conditions, whereas both the ring and methoxy group are tilted in the presence of H 2 . Additional studies with 3-methoxyphenol and 4-methoxyphenol isomers revealed these were tilted regardless of whether CTH conditions or H 2 gas were employed, with ring hydrogenation favored in all cases to yield 3-methylcyclohexanol and 4-methylcyclohexanol respectively as major products.…”
Section: Catalytic Transfer Hydrogenolysismentioning
confidence: 98%
“…ATR-IR has been employed to understand the mechanism of methoxyphenol HDO/hydrogenolysis over RANEY Ni, for which C–O cleavage is favored under CTH conditions, but ring saturation occurs under H 2 . ATR-IR measurements suggest 2-methoxyphenol lies flat with the aromatic ring parallel to the surface, favoring demethoxylation (DMO) of 2-methoxyphenol to cyclohexanol under CTH conditions, whereas both the ring and methoxy group are tilted in the presence of H 2 . Additional studies with 3-methoxyphenol and 4-methoxyphenol isomers revealed these were tilted regardless of whether CTH conditions or H 2 gas were employed, with ring hydrogenation favored in all cases to yield 3-methylcyclohexanol and 4-methylcyclohexanol respectively as major products.…”
Section: Catalytic Transfer Hydrogenolysismentioning
confidence: 98%
“…The ATR-IR spectra revealed that the adsorbed guaiacol assumes a parallel orientation to the catalyst surface, which allows a strong interaction between the methoxy CeO bond and the surface of catalyst. Conversely, the adsorption of 3-or 4methoxyphenol leads to a tilted surface complex in which the methoxy CeO bond establishes no interaction with the catalyst [9].…”
Section: Catalytic Transfer Hydrogenation/ Hydrogenolysismentioning
confidence: 99%
“…Catalytic transfer hydrodemethoxylation‐hydrogenation of guaiacol over Raney® Ni yielded 95 % cyclohexanol using isopropanol as a hydrogen source (Table 1, entry 1) [67] . Use of methanol as a hydrogen source is also reported for this conversion and it gave 54 % yield of cyclohexanol using Ni/CMK catalyst (Table 1, entry 2) [68] .…”
Section: Catalytic Conversion Of Lignin‐based Compounds Into Cyclohexmentioning
confidence: 91%